A SUCCINCT ANALYSIS OF MITIGATING LIQUIDITY RISK IN ISLAMIC BANKS IN THE LIGHT OF LIQUIDITY AND RISK MANAGEMENT PRINCIPLES - Dhiraj, Naeem Suleman; Puneri, Atharyanshah; Benraheem, Hafiz (UNISSULA, 2019)
Liquidity management has been incessantly challenging for the financial institutions and especially Islamic financial institutions due to their nature of business. The convoluted nature of liquidity management impedes the task of Islamic banks in managing their liquidity efficiently. Given the intricacies of the subject matter, this paper delves into elaborating the critical aspects of liquidity management; subsequently, discusses the consequences of poor liquidity management and problems inherent in managing the latter by analyzing the real-life failure of an Islamic financial institution as a result identifying the issues that could possibly jeopardize the existence of the Islamic banks. The research aims to provide a comprehensive understanding of the liquidity management framework and furnish with effective tools to mitigate the liquidity risk for the Islamic banks.